Amendments to some scale insect names (Hemiptera: Sternorrhyncha: Coccomorpha) - Williams, D.j. (Zootaxa, 2016)
The following scale insect specific names need gender changes to agree with their genus group names in the current printed catalogues and in ScaleNet, a database of the scale insects (García Morales et al. 2016). This action is taken to agree with Article 31.2 of the International Code of Zoological Nomenclature (International Commission on Zoological Nomenclature 1999).